Emission and measurement of greenhouse gases - Folger, Steve (Callisto Reference, 2015)
Knowledge of greenhouse gas sources, emissions, measurements and management is crucial for the capture, usage, reduction and storage of greenhouse gases that play a significant role in matters like global warming and climate change. This book presents an overview of recently developed techniques, methods, and strategies regarding greenhouse gases. It includes an extensive investigation of greenhouse gases that are emitted from hydrocarbon reservoirs, vehicle transportation, agricultural landscapes, farms, etc. It also discusses the latest detection and measurement strategies. This book includes contributions from prominent experts with extensive experience in this field and will be helpful for interested readers.